1999
DOI: 10.1159/000054448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct Application of Estrogen Aimed at Lateral Septum or Dorsal Raphe Nucleus on Lordosis Behavior: Regional and Sexual Differences in Rats

Abstract: The role of estrogen in lordosis-inhibiting systems in the lateral septum or the dorsal raphe nucleus was investigated in female and male rats. Ovariectomized rats received implantation of 22-gauge guide cannulae to the bilateral or right side of the lateral septum (LS and rLS, respectively), the dorsal raphe nucleus (DRN) or bilateral cortex (CX). In castrated male rats, bilateral implantations of the cannulae to the LS were carried out (mLS). Three behavioral tests in total were performed at 2-week intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…5-HT 1A receptor function is influenced by estrogen (Jackson and Uphouse, 1998). On the other hand, estrogen does not seem to have a direct effect on the lordosis regulating function in the DRN, because direct application of the crystal estrogen into the DRN did not facilitate lordosis in subthreshold doses of estrogen-treated ovariectomized rats (Satou and Yamanouchi, 1999). Furthermore, it has been reported that the number of serotonin-immunopositive cells in the DRN is not influenced by estrogen (Lu et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…5-HT 1A receptor function is influenced by estrogen (Jackson and Uphouse, 1998). On the other hand, estrogen does not seem to have a direct effect on the lordosis regulating function in the DRN, because direct application of the crystal estrogen into the DRN did not facilitate lordosis in subthreshold doses of estrogen-treated ovariectomized rats (Satou and Yamanouchi, 1999). Furthermore, it has been reported that the number of serotonin-immunopositive cells in the DRN is not influenced by estrogen (Lu et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Sex difference in estrogen-dependent changes of synaptic number has been reported in the LS of adult rats [25]. Sensitivity of the LS neurons to estrogen shows a sex difference, because direct application of estrogen into the LS enhances lordosis in adult female rats but not in adult male rats [5]. It is probable that neonatal estrogen causes sexual differentiation of such estrogen-related mechanisms in the LS, although relationships between the sensitivity to estrogen and the density of the LS-MCG neural connections cannot be explained yet.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the lateral septum (LS) exerts a lordosis-inhibiting influence, since lordosis is facilitated by either lesions of the LS [3]or transections of the output fibers of the LS [4]. This inhibitory influence can be counteracted by estrogen directly implanted into the LS [5]of ovariectomized rats. LS neurons, as well as VMH neurons, have been reported to send axons to the MCG [6, 7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous report suggested that the role of the GABA B -receptor system in the DRN is dependent on the function of the serotonergic system in the DRN, because the inhibitory effect of baclofen on lordosis is attenuated by DRN lesions (1). However the mechanisms of inhibition in the DRN and the septum are thought to be different, because inhibition in the lateral septum, but not in the DRN is released by estrogen (22); moreover, inhibition in the DRN appears to be independent of that in the lateral septum (23).…”
Section: Introductionmentioning
confidence: 99%